Alat Pendidikan: Reward and Punishment dalam Perspektif Falsafah Pendidikan Istam - Sapri Sapri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: The success ofthe educational process is influenced by educational tool, in the form of rewards and punishment. Both have been implemented by teachers in the learning process from early days until now. Educators or teachers should give their best to motivate each of their students by selecting the best educational toot. Therefore, we needs a proper understanding of this concept of reward and punishment. In addition, educators may only use reward and punishment as motivation. Reward and punishment must be carried out in accordance with the principtes contained in the teachings of Islam. The use of rewards is more effective than punishment, therefore, punishment may be used when other atternatives are not able to solve problems facing children. Keywords: Reward, punishment, motivation, philosophy of Islamic Education.